From a false sense of safety to resilience under uncertainty - Heino, Matti T. J.; Proverbio, Daniele; Saurio, Kaisa; Siegenfeld, Alexander; Hankonen, Nelli (Frontiers in Psychology, 2024)
Understanding and acting upon risk is notably challenging, and navigating complexity with understandings developed for stable environments may inadvertently build a false sense of safety. Neglecting the potential for non-linear change or "black swan" events – highly impactful but uncommon occurrences - may lead to naive optimisation under assumed stability, exposing systems to extreme risks. For instance, loss aversion is seen as a cognitive bias in stable environments, but it can be an evolutionarily advantageous heuristic when complete destruction is possible. This paper advocates for better accounting of non-linear change in decision-making by leveraging insights from complex systems and psychological sciences, which help to identify blindspots in conventional decision-making and to develop risk mitigation plans that are interpreted contextually. In particular, we propose a framework using attractor landscapes to visualise and interpret complex system dynamics. In this context, attractors are states towards which systems naturally evolve, while tipping points – critical thresholds between attractors – can lead to profound, unexpected changes impacting a system's resilience and well-being. We present four generic attractor landscape types that provide a novel lens for viewing risks and opportunities, and serve as decision-making contexts. The main practical contribution is clarifying when to emphasise particular strategies – optimisation, risk mitigation, exploration, or stabilisation – within this framework. Context-appropriate decision making should enhance system resilience and mitigate extreme risks.